2019
DOI: 10.14701/ahbps.2019.23.3.211
|View full text |Cite
|
Sign up to set email alerts
|

ABO-incompatible liver transplantation using only rituximab for patients with low anti-ABO antibody titer

Abstract: Backgrounds/Aims Graft survival after ABO-incompatible (ABOi) living donor liver transplantation (LDLT) has increased due to advances in desensitization methods. We analyzed early outcomes following ABOi LDLT using only rituximab without any additional desensitization methods in recipients with low anti-ABO antibody titers (≤1:32). Methods Ten adult patients underwent ABOi LDLT between September 2014 and December 2016. All patients were administered a single dose of rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, recent studies reported no significant correlation between the IA titer and AMR [ 9 , 10 ]. Consequently, several centers have proposed modified desensitization protocols [ 11 - 13 ]. The omission of plasmapheresis is a prominent change in these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies reported no significant correlation between the IA titer and AMR [ 9 , 10 ]. Consequently, several centers have proposed modified desensitization protocols [ 11 - 13 ]. The omission of plasmapheresis is a prominent change in these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the evidence for RTX monotherapy is still debated, our institution is selectively implementing RTX monotherapy when the baseline initial IA tier is low (<1:32) [ 4 ]. Otherwise, plasmapheresis combined with RTX is used as protocol to reduce the IA titer by 1:16 or lower.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the lack of sufficient evidence for the role of plasmapheresis, it is unclear whether plasmapheresis is necessary for all patients undergoing ABOi LDLT. Several studies have reported that sufficient DSZ for ABOi LDLT can be achieved using RTX alone [ 4 - 6 ]. In our center, if the baseline IA titer (≤1:32) is low, ABOi LDLT is carried out using conventional immunosuppression and RTX alone [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ABO incapability is not an absolute contraindication for successful transplantation, in urgent cases transplantation from ABO incompatible donors may be considered when no other options are available. Various approaches to remove ABO barrier and thus to broad the pool of available donors have been developed[ 10 , 11 ].…”
Section: Immunological Considerations In Liver Transplantationmentioning
confidence: 99%